Spatial Design in Schools: Impacts on Learning Potential of Children with Learning Disabilities - Datta, Soma Mandal (Curtin University, 2014)
This thesis explores the influence of built environments on human behaviour through an inter-disciplinary study across architecture, education and environmental psychology with specific focus on aiding learning for primary school students with learning problems and the relevance of current design approaches to pedagogical inclusion policies. The study is noteworthy since it bridges inter and intra-disciplinary gaps while also demonstrating that inclusive school architecture significantly enhances teaching and learning processes, specifically for children with learning disabilities.